Role of magnetic resonance imaging in the diagnosis of recurrent cancer of the cervix uteri - Z. N. Shavladze; T. P. Berezovskaya; A. A. Proshin; L. I. Krikunova; L. S. Mkrtchyan (Опухоли женской репродуктивной системы)
Objective: to define a role of magnetic resonance imaging (MRI) in the follow-up of patients with cancer of the cervix uteri (CCU), who have undergone radiation therapy and chemoradiation therapy and to describe the types of the MRI pattern of recurrent CCU in the pelvic region.Materials and methods. The results of a follow-up of 82 patients with a 4-47- (median 12 months) month history of invasive CCU were analyzed.Results. Out of the 82 patients with invasive CCU, 25 were found to have pelvic recurrences; in 23 cases MRI revealed the latter (in the cervix uteri (n = 6), corpus uteri (n = 2), vagina (n = 2), parametrium (n = 2), iliac (n = 10), paraaortic (n = 5) lymph nodes, and pelvic wall (n=5).Conclusion. The findings suggest that pelvic MRI is an effective technique to detect and estimate the extent of a pelvic recurrence and it is expedient to incorporate it into the scope of a follow-up after radiation therapy and chemoradiation therapy in patients with invasive CCU.